THE FOUNDATION AND DEVELOPMENT OF THE TOMSK SCHOOL PSYCHOLOGISTS (TO 125TH ANNIVERSARY OF THE OPENING OF THE DEPARTMENT OF PHYSIOLOGY) - M. A. Medvedev; V. B. Studnitskiy; O. I. Antonov; A. V. Skvortsov; I. V. Klimenko; A. N. Baikov (Бюллетень сибирской медицины, 2014)
The history and development of the Department of Physiology of Tomsk State University (now the Department of Normal Physiology, Siberian State Medical University) and the main results and continuity of physiological functions of the digestive system doctrine has been presented.